2021
DOI: 10.1080/03650340.2021.1978073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the application of biochar on soil fertility status, and nutrition and yield of onion grown in a no-tillage system

Abstract: The study was aimed to evaluate the effect of successive applications of increasing biochar rates along with other mineral fertilizers and poultry manure on onion nutrition and yield. The experiment consisted of 2 (agricultural year) × 11 (treatments) factorial combinations over two cropping years (2017 and 2018). Thus, 11 treatments were tested as follows: C = control; MF = mineral fertilizer; PM = poultry manure; B1+ MF = 1 Mg ha −1 of biochar+MF; B1+ PM = 1 Mg ha −1 of biochar+PM; B2+ MF = 2 Mg ha −1 of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Many researchers have found that biochar has significant advantages in terms of improving soil structure, increasing soil nutrients, and ensuring better quality and increased plant yields when added to soil as an organic amendment [ 8 , 9 , 10 , 11 ]. Biochar reduces soil bulk density, increases porosity, and improves particle size distribution because of its porous structure and low bulk density.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have found that biochar has significant advantages in terms of improving soil structure, increasing soil nutrients, and ensuring better quality and increased plant yields when added to soil as an organic amendment [ 8 , 9 , 10 , 11 ]. Biochar reduces soil bulk density, increases porosity, and improves particle size distribution because of its porous structure and low bulk density.…”
Section: Introductionmentioning
confidence: 99%
“…The provision of manure can also increase soil organic P fraction, C availability and soil microbial activity [34], as well as increasing soil CEC [33]. Application of lime to soil whether in form of dolomite, agricultural lime, biochar, straw, zeolite, Rock phosphate or plant waste can increase soil pH [19,20,23,24,25,26,28,29]. Soil pH increase will affect the availability of main nutrients for plants and will suppress the solubility of iron and aluminum.…”
Section: Discussionmentioning
confidence: 99%
“…Application of Rock phosphate-based ameliorants can increase soybean production and along with manure addition may increase the availability of P, Ca, organic matter and cation exchange capacity [24]. Ameliorant from biochar is able to increase water pH and increase the absorption of Al, Fe, Co, Cd, Ni and Zn [25,26]. Moreover, the application of ameliorant from compost affects the physical, chemical and biological processes of the soil [27]; while combination of straw and zeolite with lime can increase soil pH, cation exchange and reduce Al and Fe solubility [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is a new type of soil amendment, known as "black gold", and is used by international academics. Many researchers have shown that biochar, as an organic amendment, has significant advantages in terms of improving soil structure, increasing soil nutrients, and ensuring better quality and increasing plant yields when added to soil [9,10]. Xu [11] reported that a biochar addition rate of 3 t•ha −1 ensured stable maize yields when fertilizer application was reduced by 30%, and 3, 5 and 7 t•ha −1 biochar significantly increased maize yields at adequate nutrient levels.…”
Section: Introductionmentioning
confidence: 99%